Legal linguistics at Kyiv University: predicted conceptual model - Шевченко, Лариса Іванівна; Сизонов, Дмитро Юрійович (Київський національний університет імені Тараса Шевченка, 2021)
The article proposes a conceptual model of introduction of an innovative program into the educational process of Taras Shevchenko National University of Kyiv, which is promising for the development of communicative capabilities of the Ukrainian language and the formation of image strategies of statehood of modern Ukraine. The purpose and tasks of the new program are determined, perspective problems of legal linguistics as a neo-direction of philological science are formulated. The world experience of introduction of a new jurisprudential specialty in leading educational institutions is also analyzed, the history and modernity of world and Ukrainian legal linguistics are traced. It is proved that legal linguistics is an opportunity to use linguistic competence as a tool for learning the possibilities of language in the formalization of systematic, accurate regulatory mechanisms of social structure / social legal awareness of citizens. The article emphasizes the educational and methodological support of the specialty (textbooks, manuals, educational and methodological complexes, scientific articles), which preceded the introduction of an innovative educational program in legal linguistics. In a competitive educational space and in connection with the development of modern knowledge, the evolution of educational space is important, which meets modern social challenges, and therefore is promising for modern science. Kyiv University has always been and is an indicator of promising and modern education, where legal linguistics will take a worthy place in the professional perspective. A worthy response to competitive challenges will be a special university program in legal linguistics, where linguistic expertise will have a solid qualification basis in the complex of modern linguistic and legal knowledge.

У статті запропонована концептуальна модель впровадження в освітній процес Київського національного університету імені Тараса Шевченка інноваційної програми, що є перспективно зорієнтованою на розвиток комунікативних можливостей української мови та формування іміджевих стратегій державотворення сучасної України. Визначено мету і завдання нової програми, сформульовані перспективні проблеми юрислінгвістики як неонапряму філологічної науки. Також аналізується світовий досвід запровадження нової юрислінгвістичної спеціальності у провідних закладах освіти, прослідковується історія і сучасність світової та української юрислінгвістики. Доведено, що юрислінгвістика є можливістю застосування лінгвістичної компетенції як інструменту пізнання мови у формалізації системних, точних, світоглядно визначених регулятивних механізмів соціальної структури / соціальної правосвідомості громадян. Акцент у статті зроблено і на навчально-методичному забезпеченні спеціальності (підручники, посібники, навчально-методичні комплекси, наукові статті), які передували запровадженню інноваційної освітньої програми з юрислінгвістики. У конкурентному освітньому просторі та у зв'язку із розвитком модерних знань важливою є еволюція освітнього простору, що відповідає сучасним соціальним викликам, а отже є перспективною для сучасної науки. Київський університет завжди був і є індикатором перспективної та модерної освіти, де юрислінгвістика посяде достойне місце у фаховій комунікації. Достойною відповіддю на конкурентні виклики стане, безумовно, спеціальна університетська програма з юрислінгвістики, де мовознавча експертиза матиме ґрунтовний кваліфікаційний базис у комплексі сучасних лінгвістичних та юридичних знань.
Юрислінгвістика в Київському університеті: прогнозована концептуальна модель
Keywords: legal linguistics; linguistic expertise; innovative linguistics; neophilology.; юрислінгвістика; лінгвістична експертиза; інноваційна лінгвістика; неофілологія.